Determinasi Sustainability Report dan Rasio Keuangan terhadap Nilai Perusahaan pada Emiten Sektor Consumer Non-Cyclicals - Feny Fidyah; Allysa Fatma Indriani (Forum Kerjasama Pendidikan Tinggi, 2025)
Company value is a certain condition that has been achieved by a company as a reflection of public trust in the company after going through a process of activities for several years, namely from when the company was founded until now. Company value is very important for the company because an increase in company value will be followed by an increase in stock prices which reflect an increase in shareholder prosperity. This study aims to analyze the effect of sustainability reports, liquidity, leverage, and profitability on company value in the consumer non-cyclicals sector listed on the Indonesia Stock Exchange for the 2020-2022 period. This type of research is quantitative research. The data in this study are secondary data in the form of annual reports and sustainability reports. The sampling technique used purposive sampling so that a sample of 12 companies was obtained. The analysis technique used is multiple linear regression analysis. The results of this study indicate that the variables sustainability report, liquidity, and leverage do not affect company value, while profitability has a positive effect on company value.